Aprendizagem e desenvolvimento de competências coletivas na Secretaria de Recursos Humanos (SRH) da Universidade Federal de Campina Grande. - Lima, Jandmara de Oliveira (2013)
The objective of this study is to analyse the role of learning in the development process of collective competencies at the Human Resources Department of the Federal University of Campina Grande. With this in mind, we outlined the following objectives: (a) to describe the process of including civil servants in the professional action context; (b) to describe the learning process at the Human Resources Department; (c) to characterize the factors which facilitate and jeopardise the development of collective competencies at the SRH. The theoretical background covered the following aspects: the contextualization of staff management in Brazilian public administration; the fundamentals of learning; the social learning context; social learning: concepts and characteristics; the development of competency logics; and the development of collective competencies in the realm of social learning. The methodology used producing this study was based on the interpretative paradigm. The study corresponds to basic exploratory and qualitative research. The method used was case study. The context was the Federal University of Campina Grande, whereas the analysis unit was the Human Resources Department. For data collection we used semistructured interviews with the coordinators and the secretary of human resources, as well as two focal groups with six civil servants each. In both ways, the interviews were recorded, transcribed literally and transformed into a protocol, out of which the theme categorization was taken. For the analysis of data we used a comprehensive/interpretative analysis. The results indicate that the civil servants inclusion takes place without a determined pattern and it is conclusive in their behavior in the institution. Learning is individual and related to the management of activities. The learner context does not favour either the integration or the social learning. We also identified determining factors which enhance or make difficult the process of developing collective competencies, such as: group dynamics in the professional context; the staff; individual characteristics and dispositions motivation for learning and teaching; team integration; communication; physical structure; manager s role and Career Planning and National Policy for Staff Development. The study also showed that the development of collective competencies at the SRH is made difficult because there is no team cooperation and, consequently, no single team identity. Thus the SRH needs to re-think its learning process and the integration of its members, as well as to focus on the importance of creating an action plan which could favour social learning and the development of collective competencies.